Quetiapine versus typical antipsychotic medications for schizophrenia - Sirijit Suttajit (2018)
© 2013 The Cochrane Collaboration. Background Quetiapine is a widely used atypical antipsychotic drug for schizophrenia that has been on the market for over a decade. However, It is not clear how the effects of quetiapine differ from typical antipsychotics. Objectives To review the effects of quetiapine in comparison with typical antipsychotics in the treatment of schizophrenia and schizophrenia-like psychosis. Search methods We searched the Cochrane Schizophrenia Group Trials Register (March 2010), and inspected references of all identified studies. Selection criteria We included all randomised control trials comparing oral quetiapine with typical antipsychotic drugs in people with schizophrenia or schizophrenia-like psychosis. Data collection and analysis We extracted data independently. For dichotomous data, we calculated risk ratio (RR) and 95% confidence intervals (CI) using a random-effects model. We presented chosen outcomes in a 'Summary of findings' table and comparative risks where appropriate. For continuous data, we calculated mean differences (MD) based on a random-effects model.We assessed risk of bias for included studies. Main results The review includes 43 randomised controlled trials (RCTs) with 7217 participants. Most studies were from China. The percentages of participants leaving the studies early were similar (36.5% in quetiapine group and 36.9% in typical antipsychotics group) and no significant difference between groups was apparent for leaving early due to any reason (23 RCTs n = 3576 RR 0.91 CI 0.81 to 1.01, moderate quality evidence), however, fewer participants in the quetiapine group left the studies early due to adverse events (15 RCTs, n = 3010, RR 0.48 CI 0.30 to 0.77). Overall global state was similar between groups (no clinically significant response; 16 RCTs, n = 1607, RR 0.96 CI 0.75 to 1.23,moderate quality evidence) and there was no significant difference in positive symptoms (PANSS positive subscore: 22 RCTs, n = 1934, MD 0.02 CI -0.39 to 0.43, moderate quality evidence). General psychopathology was equivocal (PANSS general psychopathology subscore: 18 RCTs, n = 1569, MD -0.20 CI -0.83 to 0.42) between those allocated to quetiapine and typical antipsychotics. However, quetiapine was statistically significantly more efficacious for negative symptoms (PANSS negative subscore: 22 RCTs, n = 1934, MD -0.82 CI - 1.59 to -0.04, moderate quality evidence), however, this result was highly heterogeneous and driven by two small outlier studies with high effect sizes. Without these two studies, there was no heterogeneity and no statistically significant difference between quetiapine and typical antipsychotics. Compared with typical antipsychotics, quetiapine might cause fewer adverse effects (9 RCTs, n = 1985, RR 0.76 CI 0.64 to 0.90 number needed to treat to induce harm (NNTH) 10, CI 8 to 17), less abnormal ECG (2 RCTs, n = 165, RR 0.38 CI 0.16 to 0.92, NNTH 8, CI 4 to 55), fewer overall extrapyramidal effects (8 RCTs, n = 1,095, RR 0.17 CI 0.09 to 0.32, NNTH 3, CI 3 to 3, moderate quality evidence) and fewer specific extrapyramidal effects including akathisia, parkinsonism, dystonia and tremor. Moreover, it might cause lower prolactin level (4 RCTs, n = 1034, MD -16.20 CI -23.34 to -9.07, moderate quality evidence) and less weight gain compared with some typical antipsychotics in the short term (9 RCTs, n = 866, RR 0.52 CI 0.34 to 0.80, NNTH 8, CI 6 to 15). However, there was no significant difference between the two groups in suicide attempt, suicide, death, QTc prolongation, low blood pressure, tachycardia, sedation, gynaecomastia, galactorrhoea, menstrual irregularity and white blood cell count. Authors' conclusions Quetiapine may not differ from typical antipsychotics in the treatment of positive symptoms and general psychopathology. There are no clear differences in terms of the treatment of negative symptoms. However, it causes fewer adverse effects in terms of abnormal ECG, extrapyramidal effects, abnormal prolactin levels and weight gain.